Seafood substitution and mislabeling in Brussels' restaurants and canteens. (March 2018) - Christiansen, Henrik; Fournier, Nicolas; Hellemans, Bart; Volckaert, Filip A.M.
Abstract: A high demand for seafood in combination with overfishing threatens living marine resources worldwide. Sound regulation and enforcement is needed for sustainable management, yet the seafood business is characterized by high levels of uncertainty regarding product identity. Here, 280 fish dishes sold in commercial restaurants, canteens of the European Union and sushi bars throughout Brussels, Belgium were assessed for mislabeling using DNA barcoding. Overall 31.1% mislabeled samples were detected, with mislabeling present in all types of vendors. Cod and sole were the most frequently sampled and were also mislabeled regularly (13.1% and 11.1%). Bluefin tuna was substituted almost always (95% mislabeling), mostly by other tuna species. Results show that seafood labeling rules and controls are not sufficient, particularly in the food service industry, where for example commercial denominations can be ambiguous and scientific species denomination is not compulsory. Irrespective if negligent or fraudulent, mislabeling practices are detrimental for economical and sustainability goals and also consumers' trust. Highlights: 280 samples of fish dishes were collected in Brussels and molecularly tested. Mislabeling was present in cod (13.1%), sole (11.1%) and bluefin tuna (95.0%). Bluefin tuna was substituted mostly by other tuna species. The overall mislabeling rate was 31.1% and 38.1% in EU canteens.